Licófitas Arborescentes in Situ Como Elementos Importantes na Definição de Modelos Deposicionais (Formação Rio Bonito - Bacia do Paraná - Brasil) - JASPER, ANDRÉ; GUERRA-SOMMER, MARGOT (Pesquisas em Geociências, 1999)
The study of an assemblage of in situ stumps of arborescents lycopods casts in a coaly sedimentary sequence in Permian (Artinskian – Kungurian) of south brazilian Gondwana, allowed to infer a higromesofilous habita for these plants. The absence of stigmarian-like apendages suggest a root system developed in soils subjected to occasional inundation. These data confirm the depositional model proposed for these successions, related to litoraneous basins (Lagon-barrier System).